On Stability and Stabilization of Perturbed Time Scale Systems with Gronwall Inequalities - Ben Nasser, B.; Boukerrioua, K.; Hammami, M.A. (Журнал математической физики, анализа, геометрии, 2015)
In the paper, new nonlinear time scale integral inequalities are given. By means of the explicit integral bounds, we derive suffcient conditions for the uniform asymptotic stability of perturbed systems on time scales. In the sequel, basing on Lyapunov's direct method, we develop the required type of stability. В статье представлены новые нелинейные интегральные неравенства на временной шкале. С помощью явных интегральных оценок получены достаточные условия для равномерной асимптотической устойчивости возмущенных систем на временных шкалах. Далее, основываясь на прямом методе Ляпунова, разработан нужный тип стабильности.